Enhanced electrochemical performances of mesoporous carbon microsphere/selenium composites by controlling the pore structure and nitrogen doping. (20th January 2015) - Liu, Lei; Wei, Yanju; Zhang, Chuanfang; Zhang, Chuan; Li, Xu; Wang, Jitong; Ling, Licheng; Qiao, Wenming; Long, Donghui
Graphical abstract: Mesoporous carbon microspheres (MCMs) with tunable pore sizes have been prepared via a high-throughput spray drying-assisted hard template method and used as the hosts to load selenium (Se) for Li-Se batteries. Abstract: Mesoporous carbon microspheres (MCMs) with tunable pore sizes have been prepared via a high-throughput spray drying-assisted hard template method and used as the hosts to load selenium (Se) for lithium-selenium (Li-Se) batteries. The pore size control of the MCMs (3.8, 5, 6.5, 9.5 nm) was achieved by in-situ polymerized colloid silica templates with different sizes, thus prompting us to focus on tracing the effects of mesopore size on electrochemical performance of MCMs/Se cathodes. The results reveal that relative higher capacity and better cycling performance are presented in MCMs with smaller pores size due to the more effective confinement effect. At an optimal pore size of 3.8 nm, the MCMs/Se with 50% Se loading delivers an initial capacity of 513 mAh g −1 and capacity retention of 300 mAh g −1 after 100 cycles at 0.5 C. Furthermore, it is concluded that nitrogen doping could assist MCMs to retard the diffusion of polyselenide species possibly via an enhanced surface adsorption. The composites thus increase the reversible capacity by 30% after 100 cycles compared with the nitrogen-free composite. These results indicate that controlling pore structure and surface chemistry are good strategies to optimize the electrochemical performance of C/Se based cathodes for Li–Se batteries.